A cross-sectional profile and outcome assessment of adult patients triaged away from Steve Biko Academic Hospital emergency unit - Andreas Engelbrecht; F. G. du Toit; M. M. Geyser (South African Family Practice, 2015)
Background: Overcrowding is a global problem in emergency medicine. This study examined an approach to this problem at a central hospital.